Pengaruh Teknologi Artificial Intelligence (AI) dan Digital Marketing terhadap Loyalitas Pelanggan: Studi Kasus pada E-Commerce Tiktok Shop di Indonesia Tahun 2025 - Nurus Syobah; Muttaqiin, Ninnasi (Comit: Communication, Information and Technology Journal, 2025)
The development of digital technology has influenced the marketing strategies used by e-commerce players, one of which is through the use of Artificial Intelligence (AI) and digital marketing. TikTok Shop, a social media-based shopping platform, integrates AI technology and digital marketing strategies to improve customer experience. This study aims to determine the effect of AI technology and digital marketing on TikTok Shop customer loyalty. The quantitative method used was a questionnaire distributed to 60 TikTok Shop user respondents. The results showed that both AI and digital marketing have a significant influence on customer loyalty simultaneously. Partially, AI has no effect on customer loyalty, while digital marketing has an influence on customer loyalty. The conclusion is that the right integration of digital technology can be a key factor in maintaining customer loyalty in the digital era.